2015
DOI: 10.3171/2014.12.jns141775
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension of neurogenic origin: effect of microvascular decompression of the CN IX-X root entry/exit zone and ventrolateral medulla on blood pressure in a prospective series of 48 patients with hemifacial spasm associated with essential hypertension

Abstract: aBBreViatiONS AICA = anterior inferior cerebellar artery; BA = basilar artery; BP = blood pressure; CN = cranial nerve; ENMG = electroneuromyographic; GP = general practitioner; HFS = hemifacial spasm; MVD = microvascular decompression; NVC = neurovascular compression; PICA = posterior inferior cerebellar artery; REZ = root entry/exit zone; VA = vertebral artery. SuBmitted August 1, 2014. accepted December 30, 2014. iNclude wheN citiNg Published online July 31, 2015; DOI: 10.3171/2014.12.JNS141775. diSclOSure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 51 publications
1
22
1
Order By: Relevance
“…Previous studies have shown that MVD surgery could not only relieve the clinical symptoms of HFS but also improve the blood pressure management in patients with hypertension (Barley & Ellis, ; Sindou et al, ). Symptomatic treatments, such as botulinum toxin injections, medicine, and acupuncture induce, did not cause significant changes in blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that MVD surgery could not only relieve the clinical symptoms of HFS but also improve the blood pressure management in patients with hypertension (Barley & Ellis, ; Sindou et al, ). Symptomatic treatments, such as botulinum toxin injections, medicine, and acupuncture induce, did not cause significant changes in blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HFS could have concurrent hypertension. Some patients with both of these disorders were considered to share the same etiology (Miller & Selman, ; Sindou et al, ). HFS was caused by the vascular compression of the facial nerve in the REZ area in the brainstem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, studies by Jannetta et al .,[ 8 ] Geiger et al .,[ 9 ] and Sindou et al . [ 10 ] have implicated rostral VLM and root entry zone (REZ) of IX–X cranial nerves as the sites of neurogenic hypertension. [ 8 9 10 ] A significant benefit was observed by concomitant MVD of nerve V along with IX–X and VLM in patients with trigeminal neuralgia.…”
Section: Discussionmentioning
confidence: 99%